Fluorinated Unsymmetrical N, N′‐Diaryl Imidazolium Salts—New Functionalized NHC‐Ligand Precursors. Issue 27 (21st April 2017) - Topchiy, Maxim A.; Zotova, Maria A.; Masoud, Salekh M.; Mailyan, Artur K.; Ananyev, Ivan V.; Nefedov, Sergey E.; Asachenko, Andrey F.; Osipov, Sergey N.
Abstract: An efficient and scaled‐up synthesis of the imidazol‐2‐ylidene‐based unsymmetrical NHC precursors bearing the sterically demanding hexafluoroisopropylalkoxy group [(CF3 )2 (OR)C−] at the ortho position of the N ‐aryl substituent was developed. The key step of the method involved the transformation of a Mes‐substituted oxazolinium tetrafluoroborate salt through the reaction with the corresponding binucleophilic fluoroalkyl‐substituted aniline. The subsequent post‐modification of the resulting hydroxyl‐containing salt through a simple one‐step O‐alkylation protocol provided access to a new family of unsymmetrical fluorinated NHC precursors. These compounds were successfully utilized for the preparation of several novel metal complexes. The molecular structures of some NHC precursors and their metal complexes have been unambiguously characterized by single‐crystal X‐ray diffraction analysis. A preliminary evaluation of the catalytic activity of the palladium complexes was performed on a Buchwald–Hartwig amination reaction. As a result, two PEPPSI‐type (PEPPSI=pyridine‐enhanced pre‐catalyst preparation stabilization and initiation) Pd complexes have demonstrated promising activity in alkane solvents. Abstract : All in the NHC family : The synthesis of imidazole‐based unsymmetrical NHC precursors bearing the hexafluoroisopropylalkoxy group [(CF3 )2 (OR)C−] is reported (see scheme). The method includes the transformation of a Mes‐substituted oxazolinium tetrafluoroborate salt through the reaction with the corresponding binucleophilic fluorinated aniline and subsequent O‐alkylation to access a new family of fluorinated NHC precursors.